Gastropod and Bivalvia Diversity Using Environmental DNA (E-DNA) Techniques in The Waters of Gili Genting and Gili Labak Islands, Sumenep, Madura - Insafitri Insafitri; Sholihah Tsaniya Putri Radinatus; Rista Dwi Mei; Ambariyanto Ambariyanto; Nugraha Wahyu Andy (BIO Web of Conferences, 2025)
Gili Genting and Gili Labak Islands are tourist attractions that are visited by many tourists, affecting the biota in the waters, especially Gastropoda and Bivalvia. Research on the diversity of these species in Gili Genting and Gili Labak Islands has never been done before. This study aims to determine relative information on species in the waters of Gili Genting and Gili Labak. The method used in this study is the environmental DNA method to detect species through air samples, because it is considered an effective and efficient method. Sample extraction was carried out using a commercial KIT from DNeasy Blood and Tissue Kit, as well as PCR amplification using the COI (Cytochrome Oxydase subunit-1) primer. The results showed that Gili Genting Island had higher diversity and reporting values compared to Gili Labak. In Gili Genting, 5 species of Gastropoda were found including Ocenebra brevirobusta, Batillaria multiformis, Stenothyra gelasinosa, Bedeva paivae and Hemistomia cockerelli, while 3 types of Bivalvia species were found, namely Serratina capsoides, Tellinella virgata, Pinctada maculata. While Gili Labak has 4 species of Gastropoda including Priotrochus kotschyi, Diloma radula, Ocenebra brevirobusta and Steromphala umbilicaris. There are 2 species of Bivalvia, namely Lyrodus pedicellatus and Lyrodus mersinensis. The value includes the largest relative species of Gastropoda at the first location in the species Ocenebra brevirobusta with a value of 30.64% and the largest relative abundance at the second location in the species Priotrochus kostchyi with a value of 56.79%. Meanwhile, the largest Bivalvia species at the first location was the Serratina capsoides species at 52.83%, and the largest relative abundance at the second location was the Lyrodus pedicellatus species at 64.83%.